Analisis Tafsir Tarbawi terhadap Ayat-Ayat Amar Ma'ruf Nahi Munkar sebagai Basis Kontrol Sosial Siswa - Azka Abdul Hafidz; Edy Wicaksono; Umi Arofatul Lutfiyah; Rubab Wildanum Mukholladun; Fatchun Naim (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the tarbawi interpretation of the Qur’anic verses on amar ma’ruf nahi munkar as a basis for social control in shaping students’ behavior. The background of this research is the weakening of social control in educational environments, which is reflected in various forms of student behavioral deviations. This research employs a qualitative approach using a library research method by examining Qur’anic verses related to the concept of amar ma’ruf nahi munkar and analyzing interpretations from Islamic scholars within an educational perspective. The data sources consist of primary references such as the Qur’an and classical and contemporary tafsir books, as well as secondary sources including relevant books and academic journal articles. The findings indicate that the tarbawi interpretation of amar ma’ruf nahi munkar emphasizes the importance of responsibility, social awareness, and exemplary behavior as fundamental elements of social control in education. These values can be implemented in schools through habituation, collective supervision, and the strengthening of students’ religious character. This study is expected to contribute theoretically to the development of Islamic education, particularly in establishing a Qur’an-based social control system for students.